Functional Anatomy of the Craniomedial and Caudolateral Bundles of the Cranial Cruciate Ligament in Beagle Dogs - Tanegashima, Koji; Edamura, Kazuya; Akita, Yuki; Yamazaki, Atsushi; Yasukawa, Shinji; Seki, Mamiko; Asano, Kazushi; Nakayama, Tomohiro; Katsura, Taro; Hayashi, Kei (Veterinary and Comparative Orthopaedics and Traumatology, 2019)
Objective The aim of this study was to investigate detailed functional anatomy of the craniomedial bundle (CrMB) and caudolateral bundle (CdLB) of cranial cruciate ligament (CrCL) for application of intra-articular anatomical reconstruction in dogs.Materials and Methods Twelve stifle joint of 12 Beagle cadavers were used. Anatomical characteristics of femoral attachment regions of the CrCL were determined. Then, the location and area of the footprints of the CrMB and CdLB were objectively measured. Each bundle was equally divided into four fibre bundles, and changes in the fibre arrangement were recorded during stifle range of motion. Additionally, the tension of each fibre bundle at various stifle joint angles was objectively measured.Results The attachment region of the CrCL clearly differed from that reported in humans. The centre of the CdLB attachment site was located craniodistal to that of the CrMB on the femur and slightly caudal to that of the CrMB on the tibia. The area of the CrMB on the femoral and tibial attachment sites was larger than that of the CdLB. During stifle range of motion, each divided fibre bundle in the CrMB and CdLB was twisted intricately. The tension of the CrMB was higher than that of CdLB. The central part of the CrMB was always tense during stifle range of motion.Clinical Significance These results may contribute to the application of anatomical reconstruction surgery for CrCL deficient stifle in dogs.
Keywords: caudolateral bundle; craniomedial bundle; cranial cruciate ligament; dog; functional anatomy